Genome-wide analysis in response to nitrogen and carbon identifies regulators for root AtNRT2 transporters. Issue 1 (5th February 2021) - Ruffel, Sandrine; Chaput, Valentin; Przybyla-Toscano, Jonathan; Fayos, Ian; Ibarra, Catalina; Moyano, Tomas; Fizames, Cécile; Tillard, Pascal; O'Brien, Jose Antonio; Gutiérrez, Rodrigo A; Gojon, Alain; Lejay, Laurence
Abstract : A systems biology approach reveals three transcription factors involved in the regulation of NRT2 nitrate transporters in response to combinations of nitrogen and carbon treatments. Abstract: In Arabidopsis ( Arabidopsis thaliana ), the High-Affinity Transport System (HATS) for root nitrate (NO 3 − ) uptake depends mainly on four NRT2 NO 3 − transporters, namely NRT2.1, NRT2.2, NRT2.4, and NRT2.5. The HATS is the target of many regulations to coordinate nitrogen (N) acquisition with the N status of the plant and with carbon (C) assimilation through photosynthesis. At the molecular level, C and N signaling pathways control gene expression of the NRT2 transporters. Although several regulators of these transporters have been identified in response to either N or C signals, the response of NRT2 gene expression to the interaction of these signals has never been specifically investigated, and the underlying molecular mechanisms remain largely unknown. To address this question we used an original systems biology approach to model a regulatory gene network targeting NRT2.1, NRT2.2, NRT2.4, and NRT2.5 in response to N/C signals. Our systems analysis of the data identified three transcription factors, TGA3, MYC1, and bHLH093. Functional analysis of mutants combined with yeast one-hybrid experiments confirmed that all three transcription factors are regulators of NRT2.4 or NRT2.5 in response to N or C signals. These results reveal a role for TGA3, MYC1, and bHLH093 in controlling the expression of root NRT2 transporter genes.